Resin composition

By adding a diversified alcohol plasticizer in Tg ≥25 ° C to the resin composition, the problem of decreased oxygen obstruction under high humidity and difficulty melting under low humidity achieves it, and realizes that maintaining oxygen obstruction and not added water under high humidity and not added water It can also melt the effect of molding.

CN119365526APending Publication Date: 2025-01-24PLANTIC TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380047368.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-07-03
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The conventional resin composition containing modified starch and polyvinyl alcohol resin has significantly reduced oxygen barrier properties under high humidity, and is difficult to melt under low humidity, so that oxygen barrier properties and melt properties under high humidity cannot be taken into account.

Method used

By adding a multi-alcohol plasticizer with a mass of 40-150 mass in the resin composition, a polyol plasticizer containing Tg ≥25 ° C ensures that the moisture content at 23 ° C and 75 % RH is below 17.0 %, so Inhibit the reduction of oxygen obstruction under high humidity, and it can melt without adding water.

Benefits of technology

It achieves the maintenance of oxygen barrier properties under high humidity and can be melted and molded without adding water, which solves the problem of balancing oxygen barrier properties and melting properties in the existing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189697610000301
    Figure BDA0005189697610000301
  • Figure BDA0005189697610000311
    Figure BDA0005189697610000311
Patent Text Reader

Abstract

The present invention relates to a resin composition containing a modified starch (A), a polyvinyl alcohol resin (B), and a polyol plasticizer (C), the content of the polyol plasticizer (C) being 40-150 parts by mass (inclusive) per 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol resin (B), the polyol plasticizer (C) including a polyol plasticizer (c1) having a Tg of 25 DEG C or more, and the content of the polyol plasticizer (C) being 40-150 parts by mass (inclusive) per 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol resin (B). The moisture content of the resin composition is 17.0 mass% or less after the humidity is adjusted for one week at a temperature of 23 DEG C and a relative humidity of 75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent application claims priority under the Paris Convention to Japanese Patent Application No. 2022-107887 (filing date: July 4, 2022) and Japanese Patent Application No. 2022-107893 (filing date: July 4, 2022), which are hereby incorporated by reference into this specification in their entirety.

[0002] The present invention relates to a resin composition comprising modified starch, a polyvinyl alcohol-based resin and a polyol plasticizer, and a film or sheet comprising a layer composed of the resin composition. Background Art

[0003] Conventionally, resin compositions comprising modified starch and polyvinyl alcohol resins are widely used in packaging containers because they are biodegradable and have high oxygen barrier properties (e.g., Patent Document 1). In addition, resin compositions comprising modified starch, water-soluble polymers such as polyvinyl alcohol resins, polyol plasticizers, and ethylene oxide are known as biodegradable and water-washable polymers that are easily applicable to medical or industrial products and can be injection molded (e.g., Patent Document 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-6900

[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-28963 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, it is known that among the resin compositions containing modified starch and polyvinyl alcohol-based resins that can be used as biodegradable gas barrier materials, the above-mentioned conventional resin compositions containing polyol plasticizers have high oxygen barrier properties at low humidity, but show a significant decrease in oxygen barrier properties at high humidity (e.g., 75% RH) such as that exposed to food packaging films, and do not meet practical performance requirements. In addition, it is known that such resin compositions sometimes cannot be melted without adding water, and it is difficult to achieve both meltability and oxygen barrier properties at high humidity.

[0010] The present invention has been completed based on the above situation, and its purpose is to provide a resin composition comprising modified starch, a polyvinyl alcohol-based resin and a polyol plasticizer, which can suppress the reduction of oxygen barrier properties under high humidity and can be melted without adding water, and to provide a film or sheet comprising at least one layer consisting of the resin composition.

[0011] Means for solving problems

[0012] The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, it has been found that if, in a resin composition comprising modified starch (A), polyvinyl alcohol resin (B) and polyol plasticizer (C), the content of polyol plasticizer (C) is 40 parts by mass or more and 150 parts by mass or less when the total amount of modified starch (A) and polyvinyl alcohol resin (B) is 100 parts by mass, the polyol plasticizer (C) contains a polyol plasticizer (c1) having a Tg of 25° C. or more, and the resin composition has a moisture content of 17.0% by mass or less after humidity adjustment for one week at a temperature of 23° C. and a relative humidity of 75%, the above-mentioned problems can be solved, thereby completing the present invention. That is, the present invention includes the following scheme.

[0013] [1] A resin composition comprising a modified starch (A), a polyvinyl alcohol-based resin (B) and a polyol plasticizer (C), wherein the content of the polyol plasticizer (C) is 40 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol-based resin (B),

[0014] The polyol plasticizer (C) includes a polyol plasticizer (c1) having a Tg of 25°C or higher, and the resin composition has a moisture content of 17.0 mass % or less after humidity adjustment at a temperature of 23°C and a relative humidity of 75% for one week.

[0015] [2] The resin composition according to [1], wherein a mass ratio (c1 / C) of the polyol plasticizer (c1) to the polyol plasticizer (C) is 0.45 or more.

[0016] [3] The resin composition according to [1] or [2], wherein the modified starch (A) comprises a modified starch (A1) having a modifying group modified with a hydrophilic compound having an SP value greater than 11.3.

[0017] [4] The resin composition according to [3], wherein the average amylose content of the modified starch (A1) is 50% by mass or more.

[0018] [5] The resin composition according to [3] or [4], wherein the modified starch (A1) is at least one selected from etherified starch having a hydroxyalkyl group having 2 to 6 carbon atoms and esterified starch having a carboxylic acid anhydride modified group having 2 to 6 carbon atoms.

[0019] [6] The resin composition according to any one of [1] to [5], wherein the modified starch (A) comprises a modified starch (A2) having a modified group modified with a hydrophobic compound having an SP value of 11.3 or less.

[0020] [7] The resin composition according to [6], wherein the average amylose content of the modified starch (A2) is less than 50% by mass.

[0021] [8] The resin composition according to [6] or [7], wherein the modified starch (A2) is at least one selected from etherified starch having a glycidyl ether modified group having 6 to 24 carbon atoms and esterified starch having a carboxylic anhydride modified group having 6 to 24 carbon atoms.

[0022] [9] The resin composition according to any one of [6] to [8], wherein the weight average molecular weight of the modified starch (A2) is 200,000 or less.

[0023]

[10] A film or sheet comprising at least one layer comprising the resin composition according to any one of [1] to [9].

[0024] Effects of the Invention

[0025] According to the present invention, there can be provided: a resin composition comprising modified starch, a polyvinyl alcohol-based resin and a polyol plasticizer, a resin composition which can suppress the reduction of oxygen barrier properties under high humidity and can be melted without adding water, and a film or sheet comprising at least one layer consisting of the resin composition. Specific implementation plan

[0026] [Resin composition]

[0027] The resin composition of the present invention comprises a modified starch (A), a polyvinyl alcohol-based resin (B) and a polyol plasticizer (C), wherein the content of the polyol plasticizer (C) is 40 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol-based resin (B), the polyol plasticizer (C) comprises a polyol plasticizer (c1) having a glass transition temperature (sometimes referred to as Tg) of 25° C. or more, and the moisture content after humidity adjustment at a temperature of 23° C. and a relative humidity of 75% for one week is 17.0% by mass or less. It should be noted that in this specification, a polyol plasticizer (c1) having a Tg of 25°C or above is sometimes referred to as "polyol plasticizer (c1) having a Tg ≥ 25°C", "polyol plasticizer (c1)" or "polyol (c1)", and the mass ratio (c1 / C) of polyol plasticizer (c1) to polyol plasticizer (C) is sometimes referred to as "mass ratio (c1 / C)", and the moisture content after adjusting the humidity at a temperature of 23°C and a relative humidity of 75% for one week is sometimes referred to as "moisture content at 23°C and 75% RH". In addition, modified starch (A) and polyvinyl alcohol-based resin (B) are sometimes referred to as component (A) and component (B), respectively. In addition, the upper limit and lower limit values ​​described in this specification may be arbitrarily combined.

[0028] The present inventors have found that, by making the content of the polyol plasticizer (C) containing the polyol plasticizer (c1) with Tg ≥ 25°C to be 40 parts by mass or more and 150 parts by mass or less relative to a total of 100 parts by mass of the modified starch (A) and the polyvinyl alcohol resin (B), the moisture content at 23°C and 75% RH is 17.0% by mass or less, and surprisingly, the decrease in oxygen barrier properties under high humidity (e.g., 23°C and 75% RH) can be suppressed, while the melt moldability can be improved. The reason is not clear, but it is presumed that it is because both low water absorption under high humidity and the improvement of melt moldability caused by the polyol plasticizer (C) and the like can be exhibited. In addition, by making the resin composition of the present invention contain the modified starch (A1) and the modified starch (A2) described later, there is a tendency that both melt moldability and oxygen barrier properties under high humidity can be achieved at a high level. In this specification, whether the resin composition is "meltable" can be judged by whether the resin composition can be melt-molded without adding water, for example, it can be evaluated by whether the resin composition can be compression molded (or pressed) as described in the examples. This meltable characteristic is called meltability or melt moldability. In addition, in this specification, film-forming property is a characteristic showing the uniformity of the surface of the film (or sheet) obtained by melt-molding the resin composition, for example, it can be evaluated by judging whether the surface of the obtained film (or sheet) is uniform without deviation after the resin composition is extruded as described in the examples.

[0029] {Modified starch (A)}

[0030] The resin composition of the present invention contains modified starch (A). The starch as the raw material of the modified starch (A) can be derived from, for example, corn, cassava, potato, sweet potato, sago, tapioca, sorghum, bean, bracken, lotus, water chestnut, wheat, rice, oat, arrowroot, pea, etc. Among them, from the viewpoint of the content of amylose, the starch as the raw material of the modified starch (A) is preferably derived from corn or cassava, and more preferably from corn. The modified starch (A) may be composed of one or more starches. The modified starch (A) contains a modifying group that modifies the hydroxyl groups contained in the starch. From the viewpoint of being easy to reduce the increase in the moisture content of the resin composition at 23°C and 75%RH, being easy to suppress the decrease in oxygen barrier properties at high humidity, and being easy to improve melt moldability and film-forming properties, the modifying group is preferably a hydrophilic compound modifying group and / or a hydrophobic compound modifying group described later.

[0031] <Modified Starch (A1)>

[0032] The modified starch (A) preferably comprises a modified starch (A1) having a modified group modified by a hydrophilic compound having an SP value greater than 11.3. The modified group modified by the hydrophilic compound (also referred to as a modified group based on a hydrophilic compound or a hydrophilic compound modified group) is a group modified by the reaction of the reactive group of the hydrophilic compound with the hydroxyl group contained in the starch, and is preferably combined with the starch by etherification, esterification or amidation. If such a modified starch (A1) is included, it is easy to improve biodegradability and mechanical strength, and it is easy to hinder the aging of the modified starch after molding. In this specification, the SP value shows the solubility parameter calculated by Fedors' formula (Polym.Eng.Sci., 14[2], 147(1974)).

[0033] The SP value of the hydrophilic compound is preferably 12.0 or more, more preferably 12.5 or more, and further preferably 13.0 or more, and is preferably 15.5 or less, and more preferably 15.0 or less. When the SP value of the hydrophilic compound is within the above range, mechanical strength can be easily improved.

[0034] Examples of the hydrophilic compound include alkylene oxides having 2 to 6 carbon atoms, such as ethylene oxide, propylene oxide (SP value: 13.2), and butylene oxide; halogenated carboxylic acids having 2 to 4 carbon atoms, such as chloroacetic acid; halogenated alkyls having 2 to 6 carbon atoms, such as methyl bromide; carboxylic anhydrides having 2 to 6 carbon atoms, such as maleic anhydride and phthalic anhydride; oxyacid salts, such as sodium nitrate and sodium phosphate; 2-diethylaminoethyl chloride; 2,3-epoxypropyltrimethylammonium chloride, etc. Among them, at least one selected from alkylene oxides having 2 to 6 carbon atoms and carboxylic anhydrides having 2 to 6 carbon atoms is preferred from the viewpoint of reactivity with starch and ease of improving mechanical strength.

[0035] The starch as the raw material of the modified starch (A1) may be the starch exemplified as the raw material of the modified starch (A) above. The modified starch (A1) may contain one or more hydrophilic compound modification groups, and the modified starch (A) may contain one or more modified starches (A1).

[0036] In a suitable embodiment of the present invention, the average amylose content of the modified starch (A1) is preferably 50% by mass or more, more preferably 55% by mass or more, further preferably 60% by mass or more, further more preferably 65% ​​by mass or more, particularly preferably 70% by mass or more, and preferably 90% by mass or less. If the amylose content is within the above range, it is easy to reduce the increase in moisture content at 23°C and 75% RH, it is easy to suppress the decrease in oxygen barrier properties under high humidity, and it is easy to improve melt moldability and film-forming properties. In this specification, the amylose content can be measured, for example, by the iodine colorimetric method described in "Starch 50No.4 158-163 (1998)". It should be noted that, with respect to the average amylose content, when there is one type of modified starch (A1), the amylose content of the one modified starch (A1) is displayed, and when two or more types of modified starches (A1) are used, it is the content obtained by weighted average of the amylose contents of the two or more modified starches (A1). Therefore, for example, when two or more modified starches (A1) are used and the average amylose content is 50% by mass or more, a modified starch (A1) having an amylose content of less than 50% by mass may be included.

[0037] Specifically, the modified starch (A1) is preferably at least one selected from the group consisting of etherified starch, esterified starch, cationized starch, and cross-linked starch.

[0038] Examples of the etherified starch include alkyl etherified starches such as methyl etherified starch, preferably alkyl etherified starches having 2 to 6 carbon atoms; carboxyalkyl etherified starches such as carboxymethyl etherified starch, preferably carboxymethyl etherified starches having 2 to 6 carbon atoms; etherified starches having hydroxyalkyl groups such as hydroxyethylene, hydroxypropylene, and hydroxybutylene (hydroxyalkyl etherified starch), preferably etherified starches having hydroxyalkyl groups having 2 to 5 carbon atoms; allyl etherified starches, preferably allyl etherified starches having 2 to 6 carbon atoms, etc. Hydroxyalkyl etherified starches having 2 to 6 carbon atoms can be obtained by reacting starch with an alkylene oxide having 2 to 6 carbon atoms, such as ethylene oxide, propylene oxide, and butylene oxide.

[0039] Examples of esterified starch include esterified starch having a structural unit derived from acetic acid, and the like, which has a carboxylic acid-modified group (also referred to as esterified starch having a structural unit derived from carboxylic acid); esterified starch having a structural unit derived from maleic anhydride, esterified starch having a structural unit derived from phthalic anhydride, esterified starch having a structural unit derived from octenylsuccinic anhydride, and the like, which has a carboxylic acid anhydride-modified group (also referred to as esterified starch having a structural unit derived from carboxylic anhydride); esterified starch having a structural unit derived from oxygen-containing acids, such as nitrate-esterified starch, phosphate-esterified starch, and urea-phosphate-esterified starch; xanthate-esterified starch; acetoacetate-esterified starch, and the like.

[0040] Among them, from the viewpoint of improving melt moldability and film-forming property, the modified starch (A1) is preferably at least one selected from etherified starch having a hydroxyalkyl group and esterified starch having a carboxylic acid anhydride modified group, and more preferably at least one selected from etherified starch having a hydroxyalkyl group having 2 to 6 carbon atoms and esterified starch having a carboxylic acid anhydride modified group having 2 to 6 carbon atoms. In addition, in the modified starch (A1), the average number of modified hydroxyl groups per glucose unit (referred to as degree of substitution (DS)) is preferably 0.05 to 2.

[0041] In a suitable embodiment of the present invention, the weight average molecular weight (sometimes referred to as Mw) of the modified starch (A1) is preferably 200,000 or more, more preferably 250,000 or more, further preferably 300,000 or more, further more preferably 350,000 or more, particularly preferably 400,000 or more, preferably 800,000 or less, more preferably 650,000 or less, and further preferably 550,000 or less. If the Mw of the modified starch (A1) is above the above lower limit, it is easy to reduce the increase in moisture content at 23°C and 75% RH, it is easy to suppress the decrease in oxygen barrier properties under high humidity, and it is easy to improve mechanical strength. In addition, if the Mw is below the above upper limit, it is easy to improve melt moldability and film-forming properties. The weight average molecular weight of the modified starch (A1) can be measured using GPC (gel permeation chromatography), for example, it can be measured by the method described in the examples.

[0042] As modified starch (A1), commercially available products can be used, and it can also be produced by modifying a predetermined starch with a hydrophilic compound using a conventional method. Examples of representative commercial products of modified starch (A1) include ECOFILM (registered trademark) and GELOSE (registered trademark) A939, which can be obtained from Ingredion or National Starch & Chemical Company.

[0043] In one embodiment of the present invention, the content of modified starch (A1) is preferably 20% by mass or more, more preferably 30% by mass or more, preferably 100% by mass or less, more preferably 80% by mass or less, further preferably 65% ​​by mass or less, and further more preferably 50% by mass or less, relative to the mass of modified starch (A). If the content of modified starch (A1) is above the above lower limit, the mechanical strength tends to be high. In addition, if the content of modified starch (A1) is below the above upper limit, it is easy to improve melt moldability and film-forming properties.

[0044] <Modified starch (A2)>

[0045] The modified starch (A) preferably comprises a modified starch (A2) having a modified group modified by a hydrophobic compound having an SP value of less than 11.3. The modified group modified by the hydrophobic compound (sometimes referred to as a modified group based on a hydrophobic compound or a hydrophobic compound modified group) is a group modified by the reaction of the reactive group of the hydrophobic compound with the hydroxyl group contained in the starch, and is preferably combined with the starch by etherification, esterification or amidation. If such a modified starch (A2) is contained, it is easy to reduce the increase in moisture content at 23°C and 75%RH due to the reduced water absorption, and it is easy to suppress the reduction in oxygen barrier properties under high humidity, and it is easy to improve melt moldability and film forming properties.

[0046] The SP value of the hydrophobic compound is preferably 11.0 or less, more preferably 10.8 or less, and further preferably 10.5 or less, and preferably 8.0 or more, more preferably 8.4 or more, and further preferably 8.8 or more. If the SP value of the hydrophobic compound is within the above range, the water absorption of the resin composition is reduced, so it is easy to reduce the increase in water content at 23°C and 75%RH, it is easy to suppress the reduction in oxygen barrier properties under high humidity, and it is easy to improve melt moldability and film-forming properties.

[0047] The hydrophobic compound preferably contains at least one reactive group selected from, for example, a halogen group, a halohydrin group, an epoxy group, a glycidyl group, an acid anhydride group, and an amino group.

[0048] When the hydrophobic compound is etherified, i.e., bonded to starch via an ether bond, the reactive group contained in the hydrophobic compound may be, for example, a halogen group, a halohydrin group, an epoxy group, or a glycidyl group, and the hydrophobic compound is preferably a hydrophobic compound having 6 to 24 carbon atoms. Specifically, examples of the hydrophobic compound include cetyl bromide, lauryl bromide; epoxidized soybean fatty alcohol, epoxidized linseed fatty alcohol; glycidyl ethers having 2 to 24 carbon atoms such as allyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, decane glycidyl ether, lauryl phenyl glycidyl ether, myristoyl glycidyl ether, cetyl glycidyl ether, palmityl glycidyl ether, stearyl glycidyl ether, and linolyl glycidyl ether, and preferably glycidyl ethers having 6 to 24 carbon atoms.

[0049] When the hydrophobic compound is esterified, i.e., combined with starch through an ester bond, the reactive group contained in the hydrophobic compound may be, for example, an acid anhydride group, and as the hydrophobic compound, a carboxylic acid anhydride having 6 to 24 carbon atoms, preferably 7 to 20 carbon atoms, is preferred. Specifically, as the carboxylic acid anhydride, for example, alkanoic acid carboxylic acid anhydrides such as octanoic acid acetic anhydride, capric acid acetic anhydride, lauric acid acetic anhydride, and myristic acid acetic anhydride; alkyl or alkenyl dicarboxylic anhydrides such as alkyl or alkenyl succinic anhydride, alkyl or alkenyl maleic anhydride. As the alkyl or alkenyl dicarboxylic anhydride, octenyl succinic anhydride (SP value: 10.4), nonyl succinic anhydride, decyl succinic anhydride, dodecenyl succinic anhydride, octenyl maleic anhydride, nonyl maleic anhydride, decyl maleic anhydride, dodecenyl maleic anhydride, more preferably octenyl succinic anhydride or octenyl maleic anhydride.

[0050] When the hydrophobic compound is amidated, i.e., combined with starch through an amide bond, the reactive group contained in the hydrophobic compound may be, for example, an amino group. As the hydrophobic compound, an aliphatic amine containing a saturated or unsaturated hydrocarbon group having 6 to 24 carbon atoms may be suitably used. The aliphatic amine may contain a branched chain, but is preferably a straight chain. Specifically, examples of the aliphatic amine include n-dodecylamine, n-hexadecylamine, n-octadecylamine, coconut amine, tallow amine, hydrogenated N-tallow-1,3-diaminopropane, N-hydrogenated tallow-1,3-diaminopropane, and N-oleyl-1,3-diaminopropane.

[0051] Among them, the hydrophobic compound is preferably at least one selected from glycidyl ethers having 6 to 24 carbon atoms and carboxylic anhydrides having 6 to 24 carbon atoms, from the viewpoint of easily reducing the increase in the moisture content of the resin composition at 23°C and 75% RH, easily suppressing the reduction in oxygen barrier properties under high humidity, and easily improving melt moldability and film-forming properties.

[0052] The starch as the raw material of the modified starch (A2) can be exemplified as the starch as the raw material of the modified starch (A) above. The modified starch (A2) may contain one or more hydrophobic compound modification groups, and the modified starch (A) may contain one or more modified starches (A2).

[0053] In a suitable embodiment of the present invention, the average amylose content of the modified starch (A2) is preferably less than 50% by mass, more preferably less than 40% by mass, further preferably less than 30% by mass, further more preferably less than 20% by mass, particularly preferably less than 10% by mass, particularly more preferably less than 5% by mass, preferably more than 0.1% by mass, more preferably more than 0.5% by mass. If the amylose content is within the above range, it is easy to improve melt moldability and film-forming properties. It should be noted that, with respect to the average amylose content, when there is one type of modified starch (A2), the amylose content of the one modified starch (A2) is displayed, and when two or more types of modified starches (A2) are used, the content is the weighted average of the amylose content of the two or more modified starches (A2). Therefore, for example, when two or more types of modified starches (A2) are used and the average amylose content is less than 50% by mass, a modified starch (A2) having an amylose content of 50% by mass or more may be included. In the modified starch (A2), the average number of modified hydroxyl groups per glucose unit (referred to as degree of substitution (DS)) is preferably 0.05-2.

[0054] Specifically, the modified starch (A2) is preferably at least one selected from, for example, etherified starch, esterified starch and amidated starch, and more preferably at least one selected from etherified starch having 6 to 24 carbon atoms, esterified starch having 6 to 24 carbon atoms and amidated starch having 6 to 24 carbon atoms.

[0055] The etherified starch is preferably an etherified starch having a hydrophobic compound modification group, and examples of the hydrophobic compound include those exemplified above as the hydrophobic compounds used in the case of binding the hydrophobic compound to starch by etherification. The esterified starch is preferably an esterified starch having a hydrophobic compound modification group, and examples of the hydrophobic compound include those exemplified above as the hydrophobic compounds used in the case of binding the hydrophobic compound to starch by esterification. The amidated starch is preferably an amidated starch having a hydrophobic compound modification group, and examples of the hydrophobic compound include those exemplified above as the hydrophobic compounds used in the case of binding the hydrophobic compound to starch by amidation.

[0056] Among them, the modified starch (A2) is preferably at least one selected from an etherified starch having a glycidyl ether-modified group having 6 to 24 carbon atoms (etherified starch having a structural unit derived from glycidyl ether) and an esterified starch having a carboxylic anhydride-modified group having 6 to 24 carbon atoms (esterified starch having a structural unit derived from carboxylic anhydride), from the viewpoint of easily reducing an increase in the moisture content of the resin composition at 23°C and 75% RH, easily suppressing a decrease in oxygen barrier properties under high humidity, and easily improving melt moldability and film-forming properties.

[0057] In one embodiment of the present invention, the weight average molecular weight of the modified starch (A2) is preferably 200,000 or less, more preferably 190,000 or less, further preferably 180,000 or less, and may be 175,000 or less. In addition, in one embodiment of the present invention, the weight average molecular weight of the modified starch (A2) is preferably 170,000 or less, more preferably 140,000 or less, further preferably 100,000 or less, further more preferably 70,000 or less, and may be 50,000 or less. In addition, the lower limit of the weight average molecular weight of the modified starch (A2) is preferably 5,000 or more, more preferably 10,000 or more, and further preferably 20,000 or more. If the Mw of the modified starch (A2) is below the upper limit, the melt moldability and film-forming property are easily improved, and if the Mw of the modified starch (A2) is above the lower limit, the increase in moisture content at 23°C and 75% RH is easily reduced, and the decrease in oxygen barrier properties under high humidity is easily suppressed. The weight average molecular weight of the modified starch (A2) can be measured using GPC (gel permeation chromatography), for example, by the method described in the Examples.

[0058] As the hydrophobically modified starch (A2), a commercially available product may be used, or the hydrophobically modified starch may be produced by modifying a predetermined starch with a hydrophobic compound using a conventional method.

[0059] The modified starch (A) may include one or more hydrophobic modified starches (A2). In one embodiment of the present invention, two or more hydrophobic modified starches (A2) are included. From the viewpoint of easily improving the melt moldability and film-forming property of the resin composition, it is preferred that two or more modified starches (A2) with different Mw are included.

[0060] In one embodiment of the present invention, relative to the mass of modified starch (A), the content of modified starch (A2) is preferably 0 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, further more preferably 45 mass % or more, particularly preferably 55 mass % or more, preferably 80 mass % or less, more preferably 70 mass % or less. If the content of modified starch (A2) is above the above lower limit, it is easy to improve melt moldability and film-forming properties. In addition, if the content of modified starch (A2) is below the above upper limit, it is easy to improve the mechanical strength of the resin composition.

[0061] In one embodiment of the present invention, when the resin composition of the present invention comprises modified starch (A1) and modified starch (A2), the ratio of modified starch (A2) to modified starch (A1) [(A2) / (A1)] is preferably 0.1 or more, more preferably 0.5 or more, further preferably 0.8 or more, further preferably 1.2 or more, particularly preferably 1.5 or more, particularly preferably 1.8 or more, preferably 10 or less, more preferably 5 or less, further preferably 3 or less. If the ratio of modified starch (A2) to modified starch (A1) is above the above lower limit, it is easy to improve melt moldability and film-forming properties. In addition, if the content is below the above upper limit, it is easy to improve the mechanical strength of the resin composition.

[0062] {Polyvinyl alcohol resin (B)}

[0063] The resin composition of the present invention contains a polyvinyl alcohol-based resin (B). The saponification degree of the polyvinyl alcohol-based resin (B) is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 90 mol% or more, further more preferably 95 mol% or more, preferably 99.8 mol% or less, more preferably 99.5 mol% or less. When the saponification degree of the polyvinyl alcohol (B) is within the above range, the mechanical strength of the resin composition is easily improved, and the increase in water content at 23°C and 75%RH is easily reduced, and the reduction in oxygen barrier properties under high humidity is easily suppressed. It should be noted that in this specification, the saponification degree means: the molar fraction of hydroxyl groups relative to the total of hydroxyl groups and ester groups in the polyvinyl alcohol-based resin (B), which can be measured in accordance with JIS K6726.

[0064] The polyvinyl alcohol resin (B) may be a polyvinyl alcohol having a vinyl alcohol unit, or may be a modified polyvinyl alcohol containing other monomer units (also referred to as constituent units derived from other monomers) other than the vinyl alcohol unit. Examples of the other monomer units include monomer units derived from ethylenically unsaturated monomers. Examples of the ethylenically unsaturated monomer include α-olefins such as ethylene, propylene, n-butene, isobutylene, and 1-hexene; acrylic acid and its salts; unsaturated monomers having an acrylate group; methacrylic acid and its salts; unsaturated monomers having a methacrylate group; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidepropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts (e.g., quaternary salts); methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidopropanesulfonic acid and its salts, methacrylamidopropyldimethylamine and its salts (e.g., quaternary salts); methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl Vinyl ethers such as 1,3-diacetoxy-1-vinyloxypropane, 2,3-diacetoxy-1-vinyloxypropane, etc.; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate, 2,3-diacetoxy-1-allyloxypropane, and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts or esters; vinyl silyl compounds such as vinyl trimethoxysilane, isopropenyl acetate; vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl neodecanoate (vinyl In these other monomer units, the constituent units (α-olefin units) derived from α-olefins such as ethylene and propylene are preferred from the viewpoints of reducing the water absorption of the resin composition and easily reducing the increase in water content at 23°C and 75%RH, easily suppressing the reduction in oxygen barrier properties at high humidity, and easily improving melt moldability and film-forming properties. In addition, unsaponified units as monomer units derived from unsaturated monomers are also included in the other monomer units. The content of other monomer units contained in the modified polyvinyl alcohol is preferably 1 mol% or more, more preferably 3 mol% or more, further preferably 5 mol% or more, further more preferably 7 mol% or more, preferably 20 mol% or less, more preferably 15 mol% or less, can be 13 mol% or less, and can also be 10 mol% or less.When the content of other monomer units is within the above range, an increase in moisture content at 23° C. and 75% RH is likely to be reduced, a decrease in oxygen barrier properties under high humidity is likely to be suppressed, and melt moldability and film-forming properties are likely to be improved.

[0065] In one embodiment of the present invention, from the viewpoint of easily suppressing the reduction of oxygen barrier properties under high humidity and easily improving melt moldability and film forming properties, the polyvinyl alcohol-based resin (B) is preferably selected from at least one of polyvinyl alcohol and ethylene-modified polyvinyl alcohol, and more preferably ethylene-modified polyvinyl alcohol. If ethylene-modified polyvinyl alcohol is included, the water content at 23°C and 75%RH can be reduced. In the ethylene-modified polyvinyl alcohol, the content of ethylene units can be selected within the same range as the content of the other monomer units mentioned above. If the content of ethylene units is within the above range, it is easy to reduce the increase in water content at 23°C and 75%RH, it is easy to suppress the reduction of oxygen barrier properties of the resin composition under high humidity and it is easy to improve melt moldability and film forming properties. It should be noted that the content of ethylene units can be measured using NMR, etc., for example, it can be measured by the method described in the examples.

[0066] The method for producing the polyvinyl alcohol resin (B) is not particularly limited, and for example, a method in which a vinyl alcohol monomer is copolymerized with any of the other monomers, and the resulting copolymer is saponified to convert it into a vinyl alcohol unit can be cited. As the polymerization mode during copolymerization, intermittent polymerization, semi-intermittent polymerization, continuous polymerization, semi-continuous polymerization, etc. can be cited. As the polymerization method, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. The saponification of the copolymer can be applied by known methods. For example, it can be carried out in a state where the copolymer is dissolved in alcohol or aqueous alcohol. The alcohol that can be used at this time is preferably a lower alcohol such as methanol or ethanol.

[0067] The viscosity average polymerization degree (sometimes referred to as polymerization degree) of the polyvinyl alcohol resin (B) is preferably 200 or more, more preferably 220 or more, further preferably 300 or more, preferably 3000 or less, more preferably 2500 or less, further preferably 2000 or less, further more preferably 1600 or less, particularly preferably 900 or less, and particularly more preferably 600 or less. If the polymerization degree is above the lower limit, it is easy to suppress the reduction of oxygen barrier properties under high humidity and easy to improve mechanical strength. In addition, if the polymerization degree is below the upper limit, it is easy to improve melt moldability and film forming properties, and it is easy to suppress the reduction of oxygen barrier properties under high humidity. The polymerization degree of the polyvinyl alcohol resin (B) can be measured in accordance with JIS-K6726. Specifically, after the polyvinyl alcohol resin is re-saponified and purified, it is obtained by the following formula from the limiting viscosity [η] (dl / g) measured in water at 30°C (P: viscosity average polymerization degree).

[0068] P=([η]×10 3 / 8.29)(1 / 0.62)

[0069] {Polyol plasticizer (C)}

[0070] The resin composition of the present invention comprises a polyol plasticizer (C), and the content of the polyol plasticizer (C) is 40 parts by mass or more and 150 parts by mass or less relative to a total of 100 parts by mass of the modified starch (A) and the polyvinyl alcohol resin (B), and further, the polyol plasticizer (C) comprises a polyol plasticizer (c1) having a Tg ≥ 25°C. The resin composition of the present invention can suppress the reduction of oxygen barrier properties under high humidity and improve melt moldability by having the above-mentioned structure. On the other hand, if the content of the polyol plasticizer (C) is outside the above-mentioned range, it tends to have insufficient oxygen barrier properties under high humidity. The polyol plasticizer (C) is preferably a sugar alcohol.

[0071] In the resin composition of the present invention, the content of the polyol plasticizer (C) is preferably 45 parts by mass or more, more preferably 50 parts by mass or more, further preferably 55 parts by mass or more, further more preferably 60 parts by mass or more, and preferably 130 parts by mass or less, more preferably 110 parts by mass or less, based on 100 parts by mass of the total amount of the modified starch (A) and the polyvinyl alcohol-based resin (B). If the content of the polyol plasticizer (C) is above the lower limit, the melt moldability and film-forming properties of the resin composition are easily improved, and if the content of the polyol plasticizer (C) is below the upper limit, the reduction in oxygen barrier properties under high humidity is easily suppressed.

[0072] <Polyol Plasticizer (c1)>

[0073] The polyol plasticizer (c1) is a polyol having a Tg of 25°C or higher. Generally speaking, when a polyol plasticizer is added to a resin composition comprising a modified starch and a polyvinyl alcohol-based resin for the purpose of improving melt moldability, the crystallinity decreases, and the oxygen barrier properties, in particular, under high humidity, deteriorate. On the other hand, in the present invention, by containing a polyol plasticizer (c1) having a Tg ≥ 25°C so that the water content at 23°C and 75% RH is 17.0% by mass or less, not only the melting point of the resin composition is lowered and the melt moldability is improved, but also, surprisingly, the decrease in oxygen barrier properties under high humidity can be suppressed. The polyol plasticizer (c1) can be used alone or in combination of two or more.

[0074] The Tg of the polyol plasticizer (c1) is preferably 30°C or more, more preferably 35°C or more, further preferably 40°C or more, further more preferably 45°C or more, preferably 150°C or less, more preferably 130°C or less, further preferably 100°C or less, further more preferably 80°C or less, and particularly preferably 60°C or less. When the Tg of the polyol plasticizer (c1) is above the lower limit, it is easy to reduce the increase in water content at 23°C and 75%RH, and it is easy to suppress the decrease in oxygen barrier properties under high humidity. In addition, when the Tg of the polyol plasticizer (c1) is below the upper limit, it is easy to improve moldability and film-forming properties. The Tg of the polyol plasticizer (c1) can be measured using a differential scanning calorimeter, for example, by the method described in the Examples.

[0075] As the polyol plasticizer (c1), there is no particular limitation as long as the Tg is above 25°C and it is compatible with the modified starch (A) and the polyvinyl alcohol resin (B) to reduce the melting point. For example, polyols such as maltitol, trehalose, mannitol, and lactitol can be cited. They can be used alone or in combination of two or more. Among them, from the viewpoint of being easy to take into account excellent oxygen barrier properties and melt moldability, it is preferably at least one selected from maltitol, trehalose, and lactitol, more preferably maltitol and / or lactitol, and further preferably maltitol.

[0076] In the resin composition of the present invention, the mass ratio (c1 / C) of the polyol plasticizer (c1) having a Tg ≥ 25°C relative to the polyol plasticizer (C) may be 0.45 or more or 0.50 or more, preferably 0.55 or more, more preferably 0.60 or more, further preferably 0.65 or more, further more preferably 0.70 or more, particularly preferably 0.75 or more, particularly preferably 0.80 or more, and may be 0.85 or more, 0.90 or more, or 0.95 or more. If the mass ratio (c1 / C) is above the above lower limit, it is easy to reduce the increase in moisture content at 23°C and 75% RH, and it is easy to suppress the decrease in oxygen barrier properties at high humidity. The mass ratio (c1 / C) is 1.00 or less, and may be 0.97 or less. The reason why the above-mentioned effect is easily obtained when the mass ratio (c1 / C) is, for example, 0.45 or more, 0.50 or more, and preferably 0.55 or more is not clear, but it is speculated that this is because the polyol plasticizer (c1) has the effect of suppressing the water absorption of the resin composition and improving the melt moldability.

[0077] <Polyol plasticizer (c2)>

[0078] In the resin composition of the present invention, the polyol plasticizer (C) may include a polyol plasticizer (c2) having a Tg of less than 25°C or having no Tg (sometimes referred to as "polyol plasticizer (c2) having Tg < 25°C", "polyol plasticizer (c2)" or "polyol (c2)"). By including a polyol plasticizer (c2) having a Tg < 25°C, melt moldability is easily improved, but on the other hand, oxygen barrier properties under high humidity tend to decrease. The polyol plasticizer (c2) may be used alone or in combination of two or more.

[0079] The Tg of the polyol plasticizer (c2) is preferably 20°C or less, more preferably 15°C or less, further preferably 10°C or less, further more preferably 5°C or less, preferably -100°C or more, more preferably -80°C or more, further preferably -60°C or more, further more preferably -40°C or more, particularly preferably -20°C or more. If the Tg of the polyol plasticizer (c2) is above the lower limit, it is easy to suppress the reduction of oxygen barrier properties under high humidity. If the Tg of the polyol plasticizer (c2) is below the upper limit, it is easy to improve the melt moldability and film-forming properties of the resin composition. The Tg of the polyol plasticizer (c2) can be measured using a differential scanning calorimeter, for example, it can be measured by the method described in the Examples.

[0080] The polyol plasticizer (c2) is not particularly limited as long as it is a compound that can lower the Tg or melt viscosity of the modified starch (A) and the polyvinyl alcohol resin (B), and examples thereof include polyols such as sorbitol, xylitol, glycerol, and diglycerol; diols such as 1,3-butanediol and 2,3-butanediol; diols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, polypropylene glycol, trimethylene glycol, tetramethylene glycol, pentamethylene glycol, hexamethylene glycol, and propylene glycol; glycerol derivatives obtained by adding ethylene oxide, propylene oxide, etc. to polyols such as sorbitol, xylitol, glycerol, and diglycerol; pentaerythritol, sugars, polyethers; phenol derivatives such as bisphenol A and bisphenol S; amide compounds such as N-methylpyrrolidone; trimethylolpropane, diglycerol, and 3-methyl-1,3,5-pentanetriol. These may be used alone or in combination of two or more. Among them, from the viewpoint of easily improving the melt moldability and film-forming property of the resin composition, polyhydric alcohols are preferred, preferably at least one selected from sorbitol, xylitol and glycerol, and more preferably sorbitol.

[0081] In the resin composition of the present invention, the mass ratio (c2 / C) of the polyol plasticizer (c2) having a Tg of <25°C to the plasticizer (C) is preferably less than 0.45, more preferably 0.40 or less, further preferably 0.35 or less, further more preferably 0.30 or less, particularly preferably 0.20 or less, and particularly preferably 0.15 or less. If the mass ratio (c2 / C) is below the upper limit, it is easy to suppress the reduction of oxygen barrier properties under high humidity. The mass ratio (c2 / C) is 0 or more.

[0082] {Resin composition}

[0083] In the resin composition of the present invention, in addition to modified starch (A) and polyvinyl alcohol resin (B), relative to a total of 100 parts by mass of component (A) and component (B), 40 to 150 parts by mass of a polyol plasticizer (C) containing a polyol plasticizer (c1) with a Tg ≥ 25°C is also included, and the moisture content at 23°C and 75% RH is 17.0% by mass or less, so the reduction in oxygen barrier properties under high humidity can be suppressed, and it can be melted without adding water. Furthermore, in a suitable embodiment of the present invention, the resin composition of the present invention can exhibit excellent melt moldability and film-forming properties in addition to oxygen barrier properties under high humidity. Furthermore, biodegradability is also excellent. Therefore, the resin composition of the present invention can be suitably used as a material for food packaging and containers, etc.

[0084] If the moisture content of the resin composition at 23°C and 75% RH is greater than 17.0% by mass, there is a tendency that the reduction in oxygen barrier properties under high humidity is not sufficiently suppressed. The moisture content of the resin composition of the present invention at 23°C and 75% RH is 17.0% by mass or less, preferably 16.0% by mass or less, more preferably 15.9% by mass or less, further preferably 15.5% by mass or less, further more preferably 15.0% by mass or less, particularly preferably 14.5% by mass or less, particularly preferably 13.5% by mass or less, and particularly further preferably 13.0% by mass or less. If the moisture content is below the above upper limit, low water absorption performance can be exhibited even at high humidity, and the reduction in oxygen barrier properties under high humidity can be easily suppressed. The moisture content at 23°C and 75% RH is 0% by mass or more, and can also be 5% by mass or more, or 10% by mass or more. It should be noted that the moisture content is the moisture content measured at 130°C for 30 minutes using a heat-drying moisture meter after adjusting the humidity for one week under the conditions of temperature 23°C / relative humidity 75%, and can be measured, for example, by the method described in the examples. In addition, the moisture content of the resin composition of the present invention at 23°C and 75%RH can be adjusted by, for example, the molecular weight and average amylose content of the modified starch (A1), the molecular weight and average amylose content of the modified starch (A2), the type and SP value of the hydrophobic compound, the saponification degree of the polyvinyl alcohol-based resin (B), the content of ethylene-modified polyvinyl alcohol in component (B) and its ethylene modification amount, the Tg, type and content (mass ratio (c1 / C), etc.) of the polyol plasticizer (c1), etc.

[0085] The content of the modified starch (A) is preferably 40 parts by mass or more, more preferably 45 parts by mass or more, and even more preferably 48 parts by mass or more, and preferably 98 parts by mass or less, more preferably 95 parts by mass or less, even more preferably 85 parts by mass or less, and even more preferably 80 parts by mass or less, based on 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol-based resin (B). If the content of the modified starch (A) is at least the lower limit, the biodegradability is easily improved. If the content of the modified starch (A) is at most the upper limit, the decrease in oxygen barrier properties under high humidity is easily suppressed, and the melt moldability and film-forming properties are improved.

[0086] The content of the polyvinyl alcohol resin (B) is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, further preferably 15 parts by mass or more, further more preferably 20 parts by mass or more, and preferably 60 parts by mass or less, more preferably 55 parts by mass or less, further preferably 52 parts by mass or less, based on 100 parts by mass of the total amount of the modified starch (A) and the polyvinyl alcohol resin (B). If the content of the polyvinyl alcohol resin (B) is at least the lower limit, it is easy to suppress the reduction of oxygen barrier properties under high humidity and improve melt moldability and film forming properties. In addition, if the content of the polyvinyl alcohol resin (B) is at most the upper limit, it is easy to improve biodegradability. In particular, when the polyvinyl alcohol-based resin (B) is an ethylene-modified polyvinyl alcohol, its content is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, further preferably 20 parts by mass or more, and sometimes preferably 30 parts by mass or more, 40 parts by mass or more, or 45 parts by mass or more, and is preferably 70 parts by mass or less, and sometimes preferably 60 parts by mass or less, or 55 parts by mass or less, based on 100 parts by mass of the total of the modified starch (A) and the polyvinyl alcohol-based resin (B).

[0087] In the resin composition of the present invention, the total ratio of modified starch (A) and polyvinyl alcohol resin (B) relative to the mass of the resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, further more preferably 40% by mass or more, particularly preferably 50% by mass or more, preferably 70% by mass or less, more preferably 65% ​​by mass or less. If the total ratio of components (A) and (B) is above the above lower limit, it is easy to suppress the reduction of oxygen barrier properties under high humidity. In addition, if the total ratio of components (A) and (B) is below the above upper limit, it is easy to improve the melt moldability and film-forming properties of the resin composition.

[0088] The resin composition of the present invention may further contain a fatty acid having 12 to 22 carbon atoms and / or a fatty acid salt thereof. Examples of fatty acids having 12 to 22 carbon atoms and fatty acid salts thereof include stearic acid, calcium stearate, sodium stearate, palmitic acid, lauric acid, myristic acid, linoleic acid, behenic acid, and the like. Among them, stearic acid, calcium stearate, and sodium stearate are preferred from the viewpoint of processability. Fatty acids having 12 to 22 carbon atoms and fatty acid salts thereof may be used individually or in combination of two or more.

[0089] When the resin composition of the present invention contains a fatty acid having 12 to 22 carbon atoms and / or a fatty acid salt thereof, the content in the resin composition is preferably 0.01 to 3% by mass, more preferably 0.03 to 2% by mass, and further preferably 0.1 to 1% by mass relative to the mass of the resin composition. If the content of the fatty acid having 12 to 22 carbon atoms and / or a fatty acid salt thereof is within the above range, there is a tendency to be advantageous in terms of processability.

[0090] The resin composition of the present invention may further contain clay. Examples of the clay include synthetic or natural layered silicate clays, such as montmorillonite, bentonite, beidellite, mica, hectorite, saponite, nontronite, sauconite, vermiculite, ledikite, magadite, kenyaite, stevensite, volkonskoite, etc. The clay may be used alone or in combination of two or more.

[0091] When the resin composition of the present invention contains clay, the content in the resin composition is preferably 0.1 to 5% by mass, more preferably 0.1 to 3% by mass, and even more preferably 0.5 to 2% by mass relative to the mass of the resin composition. When the content of clay is within the above range, there is a tendency to be advantageous in terms of transparency and strength.

[0092] The resin composition of the present invention may contain other plasticizers in addition to the polyol plasticizer. Examples of other plasticizers include water, epoxidized linseed oil, epoxidized soybean oil, tributyl citrate, acetyl triethyl citrate, triacetin, and plasticizer resins.

[0093] The resin composition of the present invention may further contain fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, ultraviolet absorbers, heat stabilizers, light stabilizers, antioxidants, antistatic agents, flame retardants, lubricants, fragrances, foaming agents, deodorants, extenders, stripping agents, mold release agents, reinforcing materials, mildew inhibitors, preservatives, crystallization rate retardants and other additives as needed within the scope of not impairing the purpose or effects of the present invention.

[0094] In the resin constituting the resin composition of the present invention, the proportion (total proportion) occupied by the modified starch (A) and the polyvinyl alcohol resin (B) is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, further more preferably 98% by mass or more, particularly preferably 99% by mass or more, and may be 99.9% by mass or more, or 99.99% by mass or more. The resin constituting the resin composition of the present invention may also be composed only of the modified starch (A) and the polyvinyl alcohol resin (B). In the resin composition of the present invention, the proportion (total proportion) occupied by the modified starch (A), the polyvinyl alcohol resin (B) and the polyol plasticizer (C) is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, further more preferably 98% by mass or more, particularly preferably 99% by mass or more, and may be 99.9% by mass or more, or 99.99% by mass or more.

[0095] In a suitable embodiment of the present invention, the resin composition of the present invention has a low melt viscosity due to its excellent melt moldability. The complex viscosity of the resin composition of the present invention at 190°C and 10rad / s is preferably 10,500Pa·s or less, more preferably 9,000Pa·s or less, further preferably 8,000Pa·s or less, further more preferably 7,000Pa·s or less, particularly preferably 6,000Pa·s or less, particularly more preferably 5,000Pa·s or less, preferably 500Pa·s or more, more preferably 1,000Pa·s or more. If the complex viscosity is within the above range, it is easy to improve the melt moldability and film-forming property of the resin composition. The complex viscosity can be measured using a viscoelasticity measuring device, for example, by the method described in the examples. It should be noted that the complex viscosity can be used as an evaluation index for film-forming property. If the complex viscosity is large, the film-forming property tends to be low, and if the complex viscosity is small, the film-forming property tends to be high.

[0096] In a suitable embodiment of the present invention, the oxygen permeability (cc·20 μm / (m 2 ·day·atm)) is preferably 70 or less, more preferably 60 or less, further preferably 50 or less, further more preferably 40 or less, particularly preferably 20 or less, particularly more preferably 15 or less, and particularly further preferably 10 or less. If the oxygen permeability at a temperature of 23°C and a relative humidity of 75% is below the above upper limit, excellent oxygen barrier properties under high humidity are exhibited. The oxygen permeability can be measured using an air permeability measuring device after adjusting the humidity for one week under the conditions of a temperature of 23°C / relative humidity of 75%, and is the permeability when the thickness is converted to 20 μm. For example, it can be measured by the method described in the examples.

[0097] The resin composition of the present invention may be in the form of pellets, films or sheets.

[0098] [Method for producing resin composition]

[0099] The method for producing the resin composition of the present invention is not particularly limited, but preferably comprises at least a step (1) of mixing the modified starch (A), the polyvinyl alcohol-based resin (B) and the plasticizer (C) to obtain a mixture, a step (2) of extruding the mixture, and a step (3) of cooling and drying the extruded mixture.

[0100] Step (1) is a step of mixing at least the modified starch (A), the polyvinyl alcohol-based resin (B) and the plasticizer (C), and any other components such as the above-mentioned additives may be mixed together.

[0101] The step (1) is usually carried out using an extruder. In the extruder, shear stress is applied to the components by the screw, and external heat is applied to the barrel to uniformly mix the components while heating them.

[0102] As an extruder, for example, a twin-screw extruder can be used. The twin-screw extruder can be either co-rotating or counter-rotating. The screw diameter is, for example, 15 to 150 mm, and the ratio L / D of the extruder length (L) to the screw diameter (D) can be, for example, 20 to 50. The rotation speed of the screw is preferably above 80 rpm, more preferably above 100 rpm. In addition, the extrusion molding pressure is preferably above 5 bar (0.5 MPa) and more preferably above 10 bar (1.0 MPa). Each component can be directly introduced into the extruder. In addition, the mixture obtained by pre-mixing these components using a mixer can also be introduced into the extruder.

[0103] In step (1), water is preferably added from the viewpoint of improving the miscibility of the resin composition. Relative to the mass of the mixture, the amount of water added is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 10% by mass or more, further more preferably 15% by mass or more, particularly preferably 20% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, further preferably 40% by mass or less. It should be noted that the mass of the mixture is the mass of the mixture including water. In step (1), water may be introduced in the initial stage of extrusion, and water may be introduced before the above-mentioned heating temperature is reached, for example, at a temperature below 100°C. The modified starch (A) may be gelatinized by applying a cooking treatment with a combination of water, heat and shear stress. In addition, the polyvinyl alcohol resin (B) may be dissolved by introducing water, so that the resin composition is softened and the modulus and brittleness are reduced.

[0104] In step (1), the cooking treatment is preferably performed by heating at a temperature of 100°C to 160°C, more preferably 115°C to 150°C. Here, the cooking treatment refers to a treatment to break and gelatinize starch granules. Heating can be performed by applying heat to the barrel of the extruder from the outside. The target temperature can be heated by applying a step-by-step temperature change to each barrel. When the cooking treatment is performed at a temperature of 120°C or more, it is advantageous in terms of processability.

[0105] In order to prevent foaming, the cooked mixture may be pushed toward the die while lowering the temperature to preferably 80 to 120° C., more preferably 85 to 110° C. In addition, by exhausting the cylinder, foaming can be prevented and water can be removed.

[0106] The residence time in the extruder can be set according to the temperature profile or the screw speed, and is preferably 1 to 2.5 minutes.

[0107] In the step (2) of extruding the mixture, the molten mixture is pushed in the extruder while being melt-kneaded and extruded from the die. The temperature of the die is preferably 70 to 120°C, more preferably 75 to 110°C.

[0108] In the step (3) of cooling and drying the extruded mixture (melt), the mixture (melt) may be extruded in the form of a film (or sheet) or a strand.

[0109] In the case of extruding the mixture in the form of a film (or sheet), the mixture is extruded from a film forming die and then cooled and dried while being wound with a traction roller. Between the die and the roller, cooling is preferably performed to prevent the mixture from adhering to the roller. For drying, the roller may be heated, or dehumidified air may be supplied during winding. In the case of the blow-in tube method, dehumidified air may be used to expand the film as it exits the die. Talc may also be incorporated into the air stream to prevent adhesion of the film.

[0110] When the mixture is extruded in the form of strands, the strands can be extruded from a porous strand nozzle and cut with a rotary cutter to form pellets. To prevent the pellets from sticking, vibration can be applied periodically or constantly, and moisture in the pellets can be removed by hot air, dehumidified air or infrared heaters.

[0111] The resin composition of the present invention (preferably a granular resin composition) can be formed into a molded product of any shape such as a film, a sheet, a tube, a bottle, etc. by melt molding. As the melt molding method, for example, extrusion molding, injection molding, film-making method by extrusion from a T-die, inflation film-making method, compression molding method, transfer molding method, reinforced plastic molding method, hollow molding method, compression molding method, blow molding method, calendar molding method, foam molding method, vacuum molding method, gas pressure molding method and other conventional methods can be listed.

[0112] In one embodiment of the present invention, when the resin composition (e.g., granular resin composition) is compression molded, a conventional compression molding machine can be used to form a molded product. The temperature during compression molding can be appropriately adjusted according to the application, for example, it can be 100 to 300°C, preferably 120 to 250°C, or 180 to 220°C, or 190 to 215°C. The load can be, for example, 50 to 200 kgf / cm 2 , preferably 70~150kgf / cm 2 .

[0113] In one embodiment of the present invention, when a resin composition (e.g., a granular resin composition) is extruded, a molded product can be formed using a conventional extruder. As an extruder, for example, a single-screw extruder, a twin-screw extruder, etc. can be cited. The screw diameter of the extruder is, for example, 15 to 150 mm, the ratio L / D of the extruder length (L) and the screw diameter (D) is, for example, 15 to 50, and the rotation speed of the screw is preferably 80 rpm or more, more preferably 100 rpm or more. The barrel temperature in the extruder is, for example, 180 to 220° C., preferably 190 to 210° C. In other embodiments of the present invention, as extrusion conditions, the same method as the method described in [method for producing a resin composition] can be adopted.

[0114] [Film or sheet]

[0115] The present invention includes a film or sheet containing at least one layer (sometimes referred to as a resin layer) composed of a resin composition. Since the film or sheet of the present invention includes a layer composed of the resin composition of the present invention, it is excellent in oxygen barrier properties and biodegradability under high humidity. Furthermore, in a suitable embodiment of the present invention, the film or sheet of the present invention includes a resin layer formed from a resin composition having excellent film-forming properties, so there is no deviation and the surface is uniform.

[0116] The film or sheet of the present invention may be a single-layer film or sheet consisting of a resin layer, or may be a multilayer film or sheet comprising two or more resin layers, or comprising one or more resin layers and one or more other layers. In the case of comprising two or more resin layers, the composition of the resin composition constituting the resin layers may be the same or different.

[0117] The other layers are not particularly limited, and examples thereof include paper, polymer films, adhesives, etc. The paper is not particularly limited, and examples thereof include kraft paper, high-quality paper, molded paper, glassine paper, parchment paper, synthetic paper, whiteboard paper, manila paper, milk carton base paper, cup base paper, ivory paper, silver paper, etc.

[0118] There are no particular limitations on the polymer film, and examples thereof include polyethylene terephthalate (PET) film, biaxially oriented polypropylene (BOPP) film, polyethylene (PE) film (preferably low-density polyethylene (LDPE) film), polylactic acid (PLA) film, polybutylene succinate (PBS) film, polyhydroxyalkanoic acid (PHA) film, and polybutylene adipate terephthalate (PBAT) film.

[0119] When the film or sheet of the present invention is a single-layer film or single-layer sheet, it can be manufactured by extruding it from an extruder in a film (or sheet) form as described in the above-mentioned [method for manufacturing a resin composition], or after manufacturing a granular resin composition, the film or sheet can be manufactured using the above-mentioned melt molding method.

[0120] When the film or sheet of the present invention is a multilayer film or multilayer sheet, the following layer structures can be listed as the multilayer film or multilayer sheet: paper / resin layer; polymer film / resin layer; paper / adhesive / resin layer; polymer film / adhesive / resin layer; polymer film / adhesive / resin layer / paper / adhesive / polymer film.

[0121] In one embodiment of the present invention, the method for producing a multilayer film having, for example, paper / resin layer or polymer film / resin layer in sequence is preferably a method comprising the step of using an extruder to cover the resin composition on a polymer film or paper transported by a tractor.

[0122] As the extruder, for example, a single screw extruder, a twin screw extruder, etc. can be cited. The screw diameter of the extruder is, for example, 15 to 150 mm, the ratio L / D of the extruder length (L) to the screw diameter (D) is, for example, 15 to 50, and the rotation speed of the screw is preferably 80 rpm or more, more preferably 100 rpm or more. The barrel temperature in the extruder is, for example, 180 to 220° C., preferably 190 to 210° C.

[0123] The resin composition put into the extruder is plasticized and ejected from the die outlet. On the other hand, the paper or polymer film is transported with a tractor (preferably a roller tractor). The resin composition ejected from the die outlet is applied to the transported paper or polymer film to obtain a multilayer film. For example, a pressure roller etc. can be used to press the obtained multilayer film with a substrate and wind it into a roll with a winder.

[0124] In a preferred embodiment of the present invention, since the resin composition has excellent melt moldability, it can be melt molded without adding water as a plasticizer in an extruder. In addition, since the water content of the resin composition is low, it does not need to be subjected to a drying step during film formation.

[0125] In addition, a multilayer film or multilayer sheet including an adhesive can be produced by laminating, for example, paper, a polymer film, and a resin layer via an adhesive.

[0126] The thickness of the film or sheet of the present invention can be appropriately selected according to the number of layers or application, and is not limited, but is preferably 5 to 1000 μm, more preferably 10 to 500 μm. The thickness of the film or sheet can be measured by a thickness meter, for example, by the method described in the Examples.

[0127] Example

[0128] The present invention is described in detail below by way of examples, but the present invention is not limited thereto.

[0129] <Test method>

[0130] (1) Oxygen permeability under high humidity

[0131] According to JIS K 7126-1:2006, the single-layer sheets obtained in the examples and comparative examples were conditioned at a temperature of 23°C and a relative humidity of 75% for one week, and then the oxygen permeability was measured at a temperature of 23°C and a relative humidity of 75% using an air permeability measuring device (GTR-30XAK manufactured by GTR TEC Co., Ltd.). The oxygen permeability when the measured single-layer sheet thickness was converted to 20 μm was defined as oxygen permeability (cc·20 μm / (m 2 ·day·atm)) is calculated.

[0132] (2) Moisture content under high humidity

[0133] The single-layer sheets obtained in the examples and comparative examples were conditioned at 23°C / 75% relative humidity for one week and then heated at 130°C for 30 minutes using a heat-drying moisture meter (MX-50 manufactured by METTLER TOLEDO) to measure the moisture content (mass %).

[0134] (3) Complex viscosity

[0135] The complex viscosity (Pa·s) of the single-layer sheets obtained in Examples and Comparative Examples at 190° C. and 10 rad / s was measured under the condition of 1 Hz using a viscoelasticity measuring device (DISCOVERY HR-2 manufactured by TA Instruments).

[0136] (4) Film-forming properties

[0137] The resin composition obtained in the examples and comparative examples was put into a Φ15 mm twin-screw extruder (manufactured by Technovel, KZW), the screw speed was set to 200 rpm, the barrel temperature was set to 200° C., melt kneading was performed, and extruded from a die head with a width of 150 mm to produce a single-layer film with a thickness of about 50 μm. The film surface of the obtained film was visually observed, and the film surface was evaluated as A when there was no deviation and uniformity, and evaluated as B when there was deviation and non-uniformity.

[0138] (5) Weight average molecular weight of modified starch (A)

[0139] The weight average molecular weight of the modified starch (A) was calculated using GPC (gel permeation chromatography, manufactured by Tosoh Corporation, HLC-8320GPC) and pullulan as a calibration curve.

[0140] (6) SP value of the compound used in the modification of modified starch (A)

[0141] The SP value of the compound used for modifying the modified starch (A) is calculated by the Fedors' formula described in Polym. Eng. Sci., 14[2], 147 (1974).

[0142] (7) Glass transition temperature (Tg) of polyol plasticizer (C)

[0143] The glass transition temperature (Tg) of the polyol plasticizer (C) was measured at a temperature increase rate of 10° C. / min under nitrogen using a differential scanning calorimeter (DSC822e, manufactured by METTLER TOLEDO).

[0144] (8) Thickness

[0145] The thickness of the single-layer sheets obtained in Examples and Comparative Examples and the single-layer films produced in the evaluation of film-forming properties were measured using a micrometer (BMD-25MX, manufactured by Mitutoyo Corporation).

[0146] <Modified starch (A1-1)>

[0147] · ECOFILM (registered trademark): corn starch modified with propylene oxide, with an amylose content of 70% by mass, obtained from Ingredion.

[0148] The SP value of propylene oxide is 13.2.

[0149] <Hydrophobic modified starch (A2-1)>

[0150] National 912 (registered trademark): corn starch modified with octenylsuccinic acid, with a weight average molecular weight of 170,000 and an amylose content of 1% by mass, obtained from Ingredion.

[0151] <Hydrophobic modified starch (A2-2)>

[0152] CAPSUL (registered trademark): corn starch modified with octenylsuccinic acid, with a weight average molecular weight of 32,000 and an amylose content of 1% by mass, obtained from Ingredion.

[0153] The SP value of octenylsuccinic acid is 10.4.

[0154] Production Example 1

[0155] [Production of polyvinyl alcohol (B-1)]

[0156] 1300 g of vinyl acetate and 500 g of methanol were placed in a separable flask equipped with a reflux cooler, a stirrer, a thermometer, a nitrogen inlet tube, and a feed port and pump for the post-addition liquid. After nitrogen substitution in the flask, the temperature of the solution in the flask was adjusted to 60°C. 0.5 g of 2,2'-azobis(isobutyronitrile) was added to the stirred solution to start polymerization. When the polymerization rate reached 30% 2.3 hours after the start of polymerization, 1000 g of methanol was added to stop the polymerization. Methanol vapor was blown into the polymer paste to remove unreacted vinyl acetate monomer to obtain a methanol solution of polyvinyl acetate. Methanol was added to the resulting solution to adjust the concentration of polyvinyl acetate to 25% by mass. 11.6 g of a 10% by mass methanol solution of sodium hydroxide was added to 400 g of the methanol solution thus adjusted under stirring, and saponification was performed at 40°C. As the saponification reaction proceeds, the gel is crushed in a pulverizer at the moment of generating a gelled product. After a total of 1 hour of saponification reaction, 1000 g of methanol is added for neutralization. After that, 1000 g of methanol is added to the white solid polyvinyl alcohol obtained by filtration, and the mixture is left to stand and washed at room temperature for 3 hours. After the above washing operation is repeated 3 times, the polyvinyl alcohol obtained by centrifugal dehydration is dried in a dryer at 70° C. for 2 days to obtain a polyvinyl alcohol (B-1) having a viscosity average degree of polymerization of 1700 and a saponification degree of 99.2 mol%. It should be noted that the viscosity average degree of polymerization and the saponification degree are measured in accordance with JIS K6726.

[0157] Production Example 2

[0158] [Production of ethylene-modified polyvinyl alcohol (B-2)]

[0159] To a continuous polymerization tank equipped with a reflux cooler, a raw material supply line, a reaction liquid withdrawal line, a thermometer, a nitrogen inlet, an ethylene inlet, and a stirring blade, 626 L / hr of vinyl acetate, 216 L / hr of methanol, and 30.3 L / hr of a 1% methanol solution of n-propyl peroxydicarbonate as an initiator were continuously supplied using metering pumps. The ethylene pressure in the polymerization tank was adjusted to 0.69 MPa. The polymerization liquid was continuously withdrawn from the continuous polymerization tank to keep the liquid level in the polymerization tank constant. The polymerization rate at the outlet of the continuous polymerization tank was adjusted to 67%. The residence time of the continuous polymerization tank was 5 hours. The temperature at the outlet of the continuous polymerization tank was 60°C. The polymerization liquid was recovered from the continuous polymerization tank, and methanol vapor was introduced into the polymerization liquid while heating it to 75°C in a warm water bath, thereby removing residual vinyl acetate and obtaining a methanol solution of ethylene-modified vinyl ester polymer. Next, at 40°C, a saponification reaction was carried out for 1 hour using sodium hydroxide as a saponification catalyst in a ratio of 0.02 to a molar ratio of 0.5% for the system water content supplied to the saponification process. The obtained polymer was immersed in methanol for washing. Then, the solvent was removed by centrifugation and dried to obtain an ethylene-modified polyvinyl alcohol (B-2) having a viscosity average polymerization degree of 400 and a saponification degree of 98.5 mol%. It should be noted that the viscosity average polymerization degree and the saponification degree were measured in accordance with JIS K6726. A methanol solution of polyvinyl acetate obtained by removing the unreacted vinyl acetate monomer after polymerization was precipitated in n-hexane, dissolved in acetone, purified by reprecipitation 3 times, and then dried under reduced pressure at 80°C for 3 days to obtain purified polyvinyl acetate. The polyvinyl acetate was dissolved in DMSO-D6 and measured at 80°C using a 500MHz proton NMR (JEOL GX-500), and the result showed that the content of ethylene units was 10 mol%.

[0160] <Polyol Plasticizer (c1)>

[0161] As the plasticizer (c1) having a Tg of 25°C or higher, the following were used.

[0162] Plasticizer (c1-1): maltitol, Tg = 47°C

[0163] Plasticizer (c1-2): Lactitol, Tg = 33°C

[0164] Plasticizer (c1-3): Trehalose, Tg = 120°C

[0165] <Polyol plasticizer (c2)>

[0166] As the polyol (c2) having a Tg of less than 25°C or having no Tg, the following were used.

[0167] Plasticizer (c2-1): Sorbitol, Tg = -4°C

[0168] Plasticizer (c2-2): xylitol, Tg = -23°C

[0169] Plasticizer (c2-3): glycerol, Tg = -75°C

[0170] <Example 1>

[0171] 18.2 parts by mass (dry mass) of modified starch (A1-1), 18.2 parts by mass of hydrophobic modified starch (A2-1), 18.2 parts by mass (dry mass) of hydrophobic modified starch (A2-2), 5.5 parts by mass of polyvinyl alcohol (B-1) and 40 parts by mass of plasticizer (c1-1) were mixed and put into a twin-screw extruder (manufactured by Technovel, KZW) of Φ15mm and L / D=45 connected to a liquid pump, and the screw speed was 200rpm. Mixing was carried out under the temperature distribution (Table 1) shown below, and water was passed through the liquid pump at C2 and put into the cylinder so that the moisture content of the extruded resin composition was 30% by mass. The resin composition extruded in a strand shape from the die was cut with a granulator and thus formed into a particle shape. Afterwards, it was dried for 72 hours with a hot air dryer at 90°C. For the resulting resin composition particles, film forming properties were evaluated according to the method described in the above-mentioned evaluation method (4). The results are shown in Tables 2 and 3.

[0172] In addition, by using a compression molding machine, the metal mold temperature was 190°C and the load was 100 kgf / cm 2 The obtained resin composition pellets were compression molded for 1 minute under the conditions of , to produce a single-layer sheet with a thickness of about 300 μm. The obtained single-layer sheet was subjected to measurement of oxygen permeability under high humidity, water content under high humidity, and complex viscosity according to the methods described in the above evaluation methods (1) to (3). The results are shown in Tables 2 and 3.

[0173] [Table 1]

[0174] Temperature distribution [℃]

[0175] C1 C2 C3 C4 C5 C6 Die head 50 80 130 140 130 90 80

[0176] <Example 2 to Example 13, Comparative Example 1 to Comparative Example 6>

[0177] The resin composition and the single-layer sheet were prepared and evaluated in the same manner as in Example 1, except that the type and content of the modified starch (A), the type and content of the PVA (B), and the type and content of the plasticizer (C) were changed as shown in Tables 2 and 3. The results are shown in Tables 2 and 3. It should be noted that in Comparative Example 5, the modified starch (A1-1) and the polyvinyl alcohol (B-1) could not be melted, so a single-layer sheet could not be prepared by the above method. In addition, the film-forming properties were evaluated only for Examples 1, 4, 5, 10, 13 and Comparative Example 4.

[0178]

[0179]

[0180] The resin compositions obtained in Examples 1 to 13 were melt moldable, and had lower oxygen permeabilities at high humidity (23°C, 75% RH) than Comparative Examples 1 to 6, i.e., higher oxygen barrier properties. Therefore, the resin composition of the present invention can suppress the decrease in oxygen barrier properties at high humidity and can be melted without adding water.

Claims

1. A resin composition comprising a modified starch (A), a polyvinyl alcohol-based resin (B) and a polyol plasticizer (C), wherein the content of the polyol plasticizer (C) is 40 parts by mass or more and 150 parts by mass or less relative to a total of 100 parts by mass of the modified starch (A) and the polyvinyl alcohol-based resin (B), the polyol plasticizer (C) comprises a polyol plasticizer (c1) having a Tg of 25° C. or more, and the resin composition has a moisture content of 17.0% by mass or less after humidity adjustment at a temperature of 23° C. and a relative humidity of 75% for one week. 2 . The resin composition according to claim 1 , wherein a mass ratio (c1 / C) of the polyol plasticizer (c1) to the polyol plasticizer (C) is 0.45 or more. 3 . The resin composition according to claim 1 , wherein the modified starch (A) comprises a modified starch (A1) having a modifying group modified with a hydrophilic compound having an SP value greater than 11.

3. 4 . The resin composition according to claim 3 , wherein the average amylose content of the modified starch (A1) is 50% by mass or more. The resin composition according to claim 3 or 4, wherein the modified starch (A1) is at least one selected from the group consisting of etherified starch having a hydroxyalkyl group having 2 to 6 carbon atoms and esterified starch having a carboxylic acid anhydride modified group having 2 to 6 carbon atoms. 6 . The resin composition according to claim 1 , wherein the modified starch (A) comprises a modified starch (A2) having a modifying group modified with a hydrophobic compound having an SP value of 11.3 or less. 7 . The resin composition according to claim 6 , wherein the average amylose content of the modified starch (A2) is less than 50% by mass.

8. The resin composition according to claim 6 or 7, wherein the modified starch (A2) is at least one selected from etherified starch having a glycidyl ether modified group having 6 to 24 carbon atoms and esterified starch having a carboxylic anhydride modified group having 6 to 24 carbon atoms. 9 . The resin composition according to claim 6 , wherein the weight average molecular weight of the modified starch (A2) is 200,000 or less. 10 . A film or sheet comprising at least one layer comprising the resin composition according to claim 1 .

Citation Information

Patent Citations

  • Moldable biodegradable polymer

    JP2014028963A

  • Resin composition and process for producing the same

    JP2019006900A

  • Partition conveyance device and article to be conveyed partition system

    JP2022107887A

  • Secure device, command execution management method and IC chip

    JP2022107893A